AMidsummer Night's Dream 3.2.25. Issue 1 (2nd January 2020) - Cop, Michael
Abstract: This essay explicates the phrase "at our stamp" from A Midsummer Night's Dream 3.2.25. This phrase has long proved problematic, but it can be understood through Shakespeare's numismatic metaphors.